2009
DOI: 10.2353/ajpath.2009.090623
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between Forms of Sheep Scrapie and Creutzfeldt-Jakob Disease Are Encoded by Distinct Prion Types

Abstract: Transmissible spongiform encephalopathies such as scrapie in sheep, Creutzfeldt-Jakob disease (CJD) in humans, and bovine sporadic encephalopathy in cattle are characterized by the accumulation of a misfolded protein: the pathological prion protein. Ever since bovine sporadic encephalopathy was discovered as the likely cause of the new variant of CJD in humans , parallels between human and animal transmissible spongiform encephalopathies must be viewed under the aspect of a disease risk for humans. In our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 48 publications
1
43
0
6
Order By: Relevance
“…In their study, the difference in GdnHCl 1/2 values was ϳ0.6 M between the two forms of CJD (GdnHCl 1/2 in vCJD, 1.85 M; GdnHCl 1/2 in MM1 sCJD, 2.45 M), which resembles the values obtained using a greater number of vCJD and sCJD cases and the CDI in this study. CSA analysis of PrP res in sCJD of the MM genotype has shown that type 1 PrP res is more stable than type 2 (7), and this observation has been extended using a rapid dot blot variation of the CSA to encompass the MV and VV genotypes in sporadic CJD cases (53). Moreover, a recent conference abstract suggests that this higher structural stability of sCJD MM1 (compared to that of sCJD MM2) is conserved when these diseases are transmitted to bank voles (40).…”
Section: Stability Differences Identified By CDI Previous Studies Ofmentioning
confidence: 98%
“…In their study, the difference in GdnHCl 1/2 values was ϳ0.6 M between the two forms of CJD (GdnHCl 1/2 in vCJD, 1.85 M; GdnHCl 1/2 in MM1 sCJD, 2.45 M), which resembles the values obtained using a greater number of vCJD and sCJD cases and the CDI in this study. CSA analysis of PrP res in sCJD of the MM genotype has shown that type 1 PrP res is more stable than type 2 (7), and this observation has been extended using a rapid dot blot variation of the CSA to encompass the MV and VV genotypes in sporadic CJD cases (53). Moreover, a recent conference abstract suggests that this higher structural stability of sCJD MM1 (compared to that of sCJD MM2) is conserved when these diseases are transmitted to bank voles (40).…”
Section: Stability Differences Identified By CDI Previous Studies Ofmentioning
confidence: 98%
“…In octa-peptide repeat insertion patients, immunohistochemical detection of PrP Sc aggregates usually shows a patchy or tigroid pattern (d-h). Conventional anti-prion immunohistochemistry is depicted either in brown (a-c, g-i) or in red color (e, f) for visualization, performed according the protocol from [124,125]. In paraffin-embedded tissue (PET) blots (a, i; [126]), prion aggregates are stained dark brown.…”
Section: Ffi-related Mutationsmentioning
confidence: 99%
“…Similarly, abnormal PrP deposits may be absent (e, thalamus) or only focally detectable in areas with spongiform alteration such as the subiculum or cerebellar molecular layer (f). a-d H&E staining; e, f anti-prion immunohistochemistry[124,125] …”
mentioning
confidence: 99%
“…Wemheuer et al proposed a correlation between classical and atypical/Nor98 scrapie in sheep and sCJD, showing that the two scrapie types share a number of striking similarities with human PrP Sc types in sCJD (Wemheuer et al, 2009) (Fig. 4).…”
Section: The Biochemical Link Between Animal and Human Prion Forms Ismentioning
confidence: 95%